Основні особливості підготовки експерта та лідера дистанційного курсу - Кухаренко, Володимир Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Розглянуто теоретичні засади підготовки експертів та лідерів дистанційного навчання з метою удосконалення програми підготовки експертів, що мають досвід розробки дистанційних курсів, проведення дистанційних занять, навички куратора змісту. Описано основні навички, які мають бути сформовані у експерта та лідера, надаються типові помилки розробників дистанційного курсу. Показано практичний бік, коли підготовка експертів та лідерів відбувається у дистанційному курсі "Експертиза дистанційного курсу", який орієнтований на досвідчених розробників дистанційних курсів та адміністраторів систем дистанційного навчання організацій. Розкрито основні завдання навчання слухачів, зокрема вони аналізували мету навчання за таксономією Блума та її досяжність, складність тексту та його оформлення, навчальну діяльність, якість тестів, систему оцінювання та інші елементи, тобто якість навчання. У пілотному навчанні результатом був звіт слухача про проведену експертизу дистанційного курсу та аналіз цієї роботи. Звертається особлива увага на підготовку експертів-лідерів та вимірювання їх компетенцій.

The paper deals with the theoretical foundations of training experts and leaders of distance learning in order to improve their training program. An expert is a specialist who has an experience in developing distance courses, conducting distance learning classes and has and uses the skills of a content curator. Leaders create the conditions for innovative changes that allow people and organizations to share their vision and move in its direction; contribute to the management and implementation of ideas. The paper describes the basic skills to be developed by an expert and a leader, provides typical mistakes of distance course developers. Training of experts and leaders was based on the distance course "Distance Course Examination" for experienced developers of distance learning courses and administrators of distance learning systems from different organizations. During the training, students analyzed the purpose of learning according to the Bloom's taxonomy and its accessibility, the complexity of the text and its design, tasks and learning activities, test quality and evaluation system as well as other elements responsible for the quality of learning. During the pilot training, the results were obtained in the form of reports of students about the examination of the distance course as well as analysis of this work was done. 47 teachers of educational institutions of Ukraine were trained and only 12 teachers successfully completed their training. Based on the results of training and taking into account the experience of emergency training during the pandemic and military actions in Ukraine, the course program has been refined. It is planned to use a team of experts, "playing" coaches and new methods for conducting distance learning. Particular attention is paid to training experts, leaders and measuring their competencies.
Distance learning expert and leader
Keywords: дистанційний курс; якість; експертиза; оцінка; експерт; лідер; distance course; quality; examination; evaluation; expert; leader